Optimization of PVA-Arabic Gum–Honey-based Electrospun Nanofibers as Candidate Carrier for Peptide and Protein Delivery - Rezeki, Ningsih; Khairurrijal,; Surini, Silvia (Pharmaceutical Sciences and Research, 2019)
Nanofibers dressing exhibit several advantageous characteristics for accelerating wound healing, such as its similar structure to the extracellular matrix (ECM), high surface area/volume ratio, high porosity and high loading capacity of drug. The nanofibers dressing which were prepared by the electrospinning technique using combination of synthetic and natural polymer excipients capable of fulfilling the ideal wound dressing criteria. This study aimed to develop nanofibers dressing prepared from polyvinyl alcohol (PVA), Arabic gum (GA) and honey by electrospinning method. This study focused on the effect of electrospinning parameters and the morphology of electrospun nanofibers of the blended solutions made from PVA (9% w/v) – GA (1% w/v) and honey (at varied concentrations of 0;1;3% w/v) with or without Triton X-100 (0.05% v/v). The effect of varied process parameters such as voltage and flow rate in electrospinning was also investigated. The blended solutions with the various concentration of honey at 0;1;3% w/v and Triton X-100 were named as FAt, FBt, and FCt, respectively, while the blended solutions without Triton X-100, were named as FA, FB, and FC. The optimum electrospining parameter were 18 KV and 5 µl/minute for FAt, FBt, and FCt; and 20 KV and 10 µl/minute for FA, FB, and FC. Electrospun nanofibers of FAt, FBt, FCt showed smoother and more uniform fibers in comparison to the nanofibers FA, FB, and FC. The average nanofibers diameter of FAt, FBt, FCt were 244±45; 266±45; 283±57 nm, respectively, while the average nanofibers diameter of FA, FB, FC was 406±140, 457±168, 594±204 nm, respectively. Higher concentration of honey increased the diameters of nanofibers. The average nanofibers diameter of FAt, FBt, and FCt were within nanoscale in range of the ECM (50-500 nm), which were suitable for accelerating wound healing. Therefore, this study indicated that PVA-GA-honey nanofibers dressing is suitable to be further developed as carrier for growth factors